The Differences of Self Regulated Learning in Senior High Schools Students in Terms of Gender and Class Specialization - Sumarlik; Hariastuti, Retno Tri; Nursalim, Mochamad (Proceeding Series of International Conference on Arts and Humanities, 2022)
This research aims to examine methodologically and empirically the differences in the level of self-regulated learning of senior high school students in science class and Social class, seen from a gender perspective. The research variable consisted of:(a)the level of self-regulated learning,(b)class specialization, and (c)gender that was measured using modified Likert scale and using self-regulated learning level. This research is quantitative. The population is the second-year students of SMA Negeri 1 Menganti Gresik. The research sample obtained is 80 samples consisting of 40 samples from 20 males and 20 females of Natural science class, and 40 samples from 20 males and 20 females of Social science class. The data analysis used the two-way ANOVA technique. ANOVA test using the help of a computer program(SPSS19.0forwindows) is used to test two variables or more and determine whether the two variances are the same or not. After conducting the different tests using two-way ANOVA with the help of SPSS 19.0, the research results gained average Natural science class and Social science class of 103.21. The results showed that the Natural science class and Social science class students were seen from the gender.